Metabasic rocks from the Variscan Schwarzwald (SW Germany): metamorphic evolution and igneous protoliths - Altherr, Rainer; Hepp, Stefan; Klein, Hans; Hanel, Michael (International journal of earth sciences, 2021)
In the Variscan Schwarzwald metabasic rocks form small bodies included within anatectic plagioclase-biotite gneisses. Many metabasites first underwent an eclogite-facies metamorphism at about 2.0 GPa and 670-700 °C, resulting in the assemblage garnet + omphacite + rutile + quartz ± epidote ± amphibole ± kyanite. Since these eclogites are nearly free of an OH-bearing phase, they underwent almost complete dehydration during subduction, suggesting formation along an average to warm top-of-the-slab geotherm of 10-13 °C/km. The age of the Variscan high-P/high-T metamorphism is > 333 Ma. After partial exhumation from ~ 65 to ~ 15 km depth, the eclogites were overprinted under increasing activity of H2O by a number of retrograde reactions. The degree of this overprint under amphibolite-facies conditions (0.4-0.5 GPa/675-690 °C) was very different. Up to now, only retrograde eclogites have been found, but some samples still contain omphacite. Kyanite is at least partially transformed to aggregates of plagioclase + spinel ± corundum ± sapphirine. On the other hand, there are amphibolites that are extensively recrystallized and show the assemblage amphibole + plagioclase + ilmenite/titanite ± biotite ± quartz ± sulphides. The last relic phase that can be found in such otherwise completely recrystallized amphibolites is rutile. After the amphibolite-facies metamorphism at ~ 333 Ma, the metabasites underwent a number of low-temperature transformations, such as sericitization of plagioclase, chloritization of amphibole, and formation of prehnite. The intimate association of metabasite bodies with gneisses of dominantly meta-greywacke compositions suggests derivation from an active plate margin. This view is corroborated by bulk-rock geochemical data. Excluding elements that were mobile during metamorphism (Cs, Rb, Ba, K, Pb, Sr, U), the concentrations of the remaining elements in most of the metabasites are compatible with a derivation from island-arc tholeiites, back-arc basin basalts or calc-alkaline basalts. Only some samples have MORB precursor rocks.
Gesehen am 30.06.2021